Markers of intestinal barrier damage in patients with chronic insomnia disorder - Cai, Yixian; Gong, Di; Xiang, Ting; Zhang, Xiaotao; Pan, Jiyang (Frontiers in Psychiatry, 2024)
Objective: Insomnia disorder stands out as one of the prevalent clinical sleep and psychiatric disorders. Prior research has unequivocally demonstrated variations in the diversity and abundance of gut microbiota among individuals with insomnia disorder. These alterations may play a direct or indirect role in the onset and progression of insomnia disorder by compromising the integrity of the intestinal barrier. This study aims to evaluate the impairment of the intestinal barrier in individuals with insomnia disorder by scrutinizing the serum functionality of this barrier. Materials and Methods: 45 patients with chronic insomnia disorder and 30 matched healthy volunteers were meticulously selected based on inclusion criteria. ELISA technology was employed to measure serum levels of diamine oxidase (DAO), D-lactic acid (D-LA), intestinal fatty acid binding protein (I-FABP), and endothelin (ET). Spearman correlation analysis was used to explore the relationship between intestinal mucosal markers and clinical characteristics. Data were analyzed using SPSS 26.0. Results: Compared to the healthy control group, the insomnia disorder group exhibited significantly elevated scores on subjective mood and sleep scales (GAD-7, PHQ-9, HAMA, HAMD, PSQI, and ISI) (P < 0.05). Overnight PSG indicated a notable increase in bed time, total wake time, sleep onset latency, and wake after sleep onset in individuals with insomnia disorder. Additionally, there was a decrease in sleep efficiency and alterations in sleep structure (increased proportion of N1 and N3 stages, prolonged N1 stage) (P < 0.05). The chronic insomnia disorder group displayed significantly reduced concentrations of serum DAO, D-LA, I-FABP, and ET (P < 0.05). Furthermore, significant positive correlations were identified between intestinal epithelial barrier markers and sleep efficiency, while negative correlations were found with wake after sleep onset, total wake time, PSQI, HAMA, and HAMD. Additionally, D-LA levels were significantly positively correlated with ET concentrations. Conclusion: Individuals with chronic insomnia disorder manifest disruptions in sleep structure, heightened susceptibility to anxiety and depressive moods, and impaired intestinal barrier function. These findings suggest that the occurrence and development of insomnia disorder may be linked to the impairment of the intestinal barrier.